Development of Project-Based Learning Oriented Teaching Materials for Elementary School Learning Media Course in the OBE-Based Merdeka Curriculum - Gusti Ayu Dewi Setiawati; Ketut Manik Asta Jaya; Kadek Yudista Witraguna; Ni Nyoman Tri Wahyuni; I Gusti Putu Suyatna Juliantara; I Komang Agus Bayu Juniarta (Universitas Negeri Malang, 2025)
Abstract: This research aims to develop project-based learning-oriented teaching materials for the elementary school learning media course in the OBE-based Merdeka Curriculum to improve the student’s learning process, using the ADDIE development model. Designed for the elementary school teacher education program at I Gusti Bagus Sugriwa Denpasar State Hindu University, the process included needs analysis, material design, development (lesson plans and modules), and validation by five experts evaluating content, media, and language. Effectiveness and practicality were assessed through lecturer and student response questionnaires. Results show the teaching material is valid and practical, with lesson plans rated “very feasible,” modules achieving a positive Content Validity Ratio (CVR > 0), and high practicality scores (93 percent and 92.65 percent). These findings indicate strong acceptance by both lecturers and students. The integration of Outcome-Based Education (OBE), the Merdeka Curriculum, and Project-Based Learning (PjBL) within a single instructional resource offers a new model connecting theory, practice, and real classroom application. Abstrak: Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis proyek untuk mata pelajaran media pembelajaran di sekolah dasar dalam Kurikulum Merdeka berbasis OBE, guna meningkatkan proses belajar siswa, yang dilakukan dengan menggunakan model pengembangan ADDIE. Dirancang untuk program studi pendidikan guru sekolah dasar di Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, prosesnya meliputi analisis kebutuhan, desain materi, pengembangan (rencana pembelajaran dan modul), serta validasi oleh lima ahli yang mengevaluasi konten, media, dan bahasa. Efektivitas dan kepraktisan dievaluasi melalui kuesioner respon dosen dan siswa. Hasil menunjukkan bahan ajar tersebut valid dan praktis, dengan rencana pembelajaran yang dinilai “sangat layak,” modul mencapai Content Validity Ratio (CVR) positif (CVR > 0), dan skor kepraktisan yang tinggi (93 persen dan 92,65 persen). Temuan ini menunjukkan penerimaan yang kuat baik dari dosen maupun siswa. Integrasi Outcome-Based Education (OBE), Kurikulum Merdeka, dan Pembelajaran Berbasis Proyek (PjBL) dalam satu sumber daya instruksional menawarkan model baru yang menghubungkan teori, praktik, dan penerapan secara nyata di kelas.